Legal Implications of Blockchain Technology for the Indonesian National Financial System and Monetary Authorities - Edmon Makarim; Edmon Makarim (Bank Indonesia, 2026)
Bank Indonesia faces significant governance challenges as it integrates blockchain technology into the national financial infrastructure. While blockchain offers enhanced transparency and operational integrity, it also raises critical concerns about security, systemic vulnerabilities, and legal accountability. This doctrinal study examines blockchain deployment within the Indonesian financial system, focusing on data protection, technical risks, and the allocation of liability for system failures or breaches. Findings indicate that while decentralised architectures can bolster transactional trust, they are constrained by smart-contract vulnerabilities and interoperability issues. Legally, determining accountability in distributed networks remains problematic, especially where centralised control is absent. Consequently, the study advocates for a comprehensive, adaptive regulatory framework anchored in public institutional authority. Such a framework must align blockchain use with statutory obligations regarding data protection and payment system governance. Grounded in Indonesia’s legal structure and international standards, this approach provides a model for jurisdictions seeking to integrate blockchain into state-supervised financial systems.